Language and the Political Condition of the Largest Stateless Nation of the World - Saeed, Mihraban Salih; Abbas, Abbas Mustafa (Sulaimani Journal for Humanities, 2018)
This paper entitled “Language and the political conditions of the largest stateless nation of the world” shows how the Kurds could survive its language and nationality. Kurds are member of an ethnic and linguistic group living in the Taurus Mountains of eastern Anatolia, the Zagros Mountains of western Iran, part of northern Iraq, Syria, and Armenia, and other adjacent areas. Most of the Kurds live in contiguous areas of Iran, Iraq, and Turkey—a somewhat loosely defined geographic region generally referred to as Kurdistan (Land of the Kurds). The name has different connotations in Iran and Iraq which officially recognize internal entities by this name.